PENDAMPINGAN BALITA DENGAN MASALAH GIZI DI KELURAHAN KARANG POH, WILAYAH KERJA PUSKESMAS BALONGSARI - Agtika Yasyfa Nur Azizah (Poltekkes Kemenkes Bengkulu, 2025)
Undernutrition is an indicator of malnutrition that affects the growth and development of children. Karang Poh Village is one of the areas that alleviate under-five nutrition problems because of the nutritional problems and the largest number of under-fives in the village. This mentoring activity aims to overcome problems in toddlers who do not gain weight, undernutrition, malnutrition, growth faltering, infant and child feeding, very premature babies, LBW babies, congenital metabolic disorders, and provide health communication, information, and education. This mentoring was carried out from March 2024 to June 2024. This activity is located in Karang Poh Village. Evaluation of the toddler assistance program with nutritional problems is seen from the results of activities in the form of coverage in the form of tables, figures, and diagrams. There was an increase in weight and height of toddlers before and after mentoring. The average increase in toddler weight during the assistance period was 1.02 kg. Meanwhile, the average increase in toddler height is 2.87 cm. The final results of the assistance in June 2024 obtained 1 toddler graduated from pre-stunting, 1 toddler graduated from stunting, and 1 toddler graduated from malnutrition. Mentoring for toddlers with nutritional problems provides good results. However, this mentoring must continue and the mentoring be carried out with more incentives.